2019
DOI: 10.1080/15548627.2019.1598750
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CA7-4 promotes autophagy and apoptosis via sponging MIR877-3P and MIR5680 in high glucose-induced vascular endothelial cells

Abstract: Vascular endothelial cells (VECs) that form the inner wall of blood vessels can be injured by high glucose-induced autophagy and apoptosis. Although the role of long noncoding RNA in regulating cell fate has received widespread attention, long noncoding RNAs (lncRNAs) that can both regulate autophagy and apoptosis need to be discovered. In this study, we identified that a small chemical molecule, 3-benzyl-5-([2-nitrophenoxy] methyl)-dihydrofuran-2(3H)-one (3BDO), synthesized by us, could inhibit VEC autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 51 publications
2
84
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs), which are more than 200 nucleotides in length, used to be very poorly understood. However, in recent years, various functions of lncRNAs have been identified, including participating in the autophagy pathway 2,3 , controlling cell differentiation 4 , and acting as competing endogenous RNAs (ceRNAs) for microRNAs 2,5 . The role of some lncRNAs as ceRNAs of miRNAs has been demonstrated in cancer metastasis and invasion [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs), which are more than 200 nucleotides in length, used to be very poorly understood. However, in recent years, various functions of lncRNAs have been identified, including participating in the autophagy pathway 2,3 , controlling cell differentiation 4 , and acting as competing endogenous RNAs (ceRNAs) for microRNAs 2,5 . The role of some lncRNAs as ceRNAs of miRNAs has been demonstrated in cancer metastasis and invasion [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Our mechanism studies underlying NORFA regulation of porcine granulosa cell apoptosis and follicular atresia have revealed that NORFA acts as a ceRNA of nearby miR-126 gene, which was upregulated during ovarian follicular atresia. The ceRNA hypothesis posits that specific RNAs, such as mRNAs, pseudogene transcripts, circular RNAs, and lncRNAs, can impair miRNA activity through acting as molecular sponges for endogenous miRNAs, thereby enhancing miRNA target expression 39,40 . Acting as a ceRNA is the main function mode for lncRNAs containing the same MREs with targets 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Such gene is called competing endogenous RNA (ceRNA), and the "RNA-miRNA" interaction appreciably extends the gene function product from protein to mRNA. Generally, non-coding RNAs such as LncRNA 2810403, CA7-4, and LncIRS1 are prone to exert biological function through ceRNA mechanism (31,32). Recently, coding genes have also been proven to regulate cell proliferation through ceRNA network.…”
Section: Discussionmentioning
confidence: 99%